2006
DOI: 10.1051/0004-6361:20064947
|View full text |Cite
|
Sign up to set email alerts
|

The role of Fischer-Tropsch catalysis in Jovian subnebular chemistry

Abstract: We examine the production of methane via Fischer-Tropsch catalysis in an evolving turbulent model of the Jovian subnebula and its implications for the composition of satellitesimals produced in situ. We show that there is a catalytically-active region in the Jovian subnebula from 65 Jupiter radii that moves inwards with time. The pressure range in this region is about 10 −4 to 10 −3 bar and implies that, if transport processes and the cooling of the subnebula are not considered, CO and CO 2 are entirely conver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…As a consequence, the presence of a catalytically active region in the subnebula implies that methane and water formed via Fischer-Tropsch catalysis are accreted with the gas onto the forming Saturn. This conclusion is similar to the one found by Mousis et al (2006b) in the case of the Jovian subnebula. Finally, we conclude that the (homogeneous or heterogeneous) chemical processes that may occur in the subnebula are likely to have no effect on the composition of ices formed in the subnebula: the CO 2 :CO:CH 4 and N 2 :NH 3 ratios in the zone of planetesimal formation (at temperatures lower than 150 K) are the same as those acquired from the solar nebula.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As a consequence, the presence of a catalytically active region in the subnebula implies that methane and water formed via Fischer-Tropsch catalysis are accreted with the gas onto the forming Saturn. This conclusion is similar to the one found by Mousis et al (2006b) in the case of the Jovian subnebula. Finally, we conclude that the (homogeneous or heterogeneous) chemical processes that may occur in the subnebula are likely to have no effect on the composition of ices formed in the subnebula: the CO 2 :CO:CH 4 and N 2 :NH 3 ratios in the zone of planetesimal formation (at temperatures lower than 150 K) are the same as those acquired from the solar nebula.…”
Section: Discussionsupporting
confidence: 92%
“…We first examine the homogeneous gas-phase reactions of C and N volatiles in Saturn's subnebula, following the approach proposed by MGB02. We also investigate the catalytic effects on the gas-phase reactions induced by the presence of iron particles mixed with hydrogen gas in Saturn's subnebula, using the experimental data of Sekine et al (2005) and following the approach proposed by Mousis et al (2006b) for the Jovian subnebula.…”
Section: Chemistry Of C-and N-bearing Volatiles In the Subnebulamentioning
confidence: 99%
“…They concluded that CH 4 -rich satellitesimals could have formed in the catalytically active region of the subnebula and thus may have played an important role in the origin of Titan's atmosphere. In contrast, investigations led by Mousis et al ( 2006 ) confirmed the likely existence of a catalytically active region in the subnebula but estimated that it has no influence on the composition of the forming satellitesimals, because the produced CH 4 is shown to be accreted by Saturn prior to its trapping in the satellites' building blocks.…”
Section: Synthesis Of Methane In Astrophysical Environmentsmentioning
confidence: 95%